2003
DOI: 10.1002/masy.200350837
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fillers on fire retardancy of intumescent polypropylene blends

Abstract: Addition of Ammonium Polyphosphate/Polyamide‐6 system is known to provide flame retardancy in many polymers blends via an intumescent process. Particulate fillers (talc and calcium carbonate) are used in large quantities in PP. Combination of fillers in PP can modify the properties of the polymeric matrix. This study investigates the effect of fillers (talc and calcium carbonate) on the fire performance of the Polypropylene/Ammonium polyphosphate/Polyamide‐6 blend. It is shown that the fire performance strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 0 publications
1
49
0
Order By: Relevance
“…Catalytic reactivity and synergistic effectivity of REO might be determined by the filling status of the 4f shell of the rare earth element. The electronic configurations of Sm and La are 4f 6 5d 1 6s 2 5d 1 6s 2 [24]. Based on the lowest energy principle, when the 4f shell is fully filled, half filled, or completely empty, it has the lowest energy and so is most stable.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…Catalytic reactivity and synergistic effectivity of REO might be determined by the filling status of the 4f shell of the rare earth element. The electronic configurations of Sm and La are 4f 6 5d 1 6s 2 5d 1 6s 2 [24]. Based on the lowest energy principle, when the 4f shell is fully filled, half filled, or completely empty, it has the lowest energy and so is most stable.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…In recent years, intumescent flame retardant (IFR) [6][7][8][9][10][11][12][13][14][15][16] is well-known as a new generation of flame retardants in polypropylene and other polyolefins for some of their merits, such as very low smoke and toxic gases produced during burning, and antidripping property, which conform to the tendency of flame retardants' development.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies [11][12][13] have indicated the usage of fillers to improve the performances of the coatings. Incorporating nano-sized fillers specifically into coatings can greatly enhance its fire resistance and anti-oxidation properties [14].…”
Section: Introductionmentioning
confidence: 99%